2011
DOI: 10.1080/03601277.2011.553560
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Geropsychologists-in-Training during Internship and Postdoctoral Fellowship Years

Abstract: Psychology internship and fellowship years are exciting yet challenging times of professional development, as geropsychologists-in-training transition to independent practice and work to consolidate their identities as professional geropsychologists. Geropsychology supervisors help interns and fellows to develop and refine attitude, knowledge, and skill competencies for geropsychology practice. Transformational geropsychology supervisors also serve as mentors. They offer professional role modeling, acknowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Bona fide professional geropsychologists using observational methods are employed as supervisors in geropsychology training programs so that students can develop appropriate skills in working with older adults. (Knight et al, 2009, p. 210) The still-small published literature on geropsychology supervision suggests that geropsychology supervisors must be prepared to address complex clinical issues that can arise among older clients and care systems, and also be made aware of common blind spots and complex relational issues that can arise as psychology trainees learn to work with diverse older adults, families, and care systems (Abeles & Ettenhoffer, 2008;Duffy & Morales, 1997;Karel, Altman, Zweig, & Hinrichsen, 2014;Karel & Stead, 2011;Knight, 2010;Qualls, Duffy, & Crose, 1995). Psychologists who have received training in formal geropsychology programs are a critical resource for the education and supervision of current and future generations of psychologists to develop competencies for work with older adults.…”
mentioning
confidence: 99%
“…Bona fide professional geropsychologists using observational methods are employed as supervisors in geropsychology training programs so that students can develop appropriate skills in working with older adults. (Knight et al, 2009, p. 210) The still-small published literature on geropsychology supervision suggests that geropsychology supervisors must be prepared to address complex clinical issues that can arise among older clients and care systems, and also be made aware of common blind spots and complex relational issues that can arise as psychology trainees learn to work with diverse older adults, families, and care systems (Abeles & Ettenhoffer, 2008;Duffy & Morales, 1997;Karel, Altman, Zweig, & Hinrichsen, 2014;Karel & Stead, 2011;Knight, 2010;Qualls, Duffy, & Crose, 1995). Psychologists who have received training in formal geropsychology programs are a critical resource for the education and supervision of current and future generations of psychologists to develop competencies for work with older adults.…”
mentioning
confidence: 99%
“…Although some supervision styles can combine the roles of a supervisor and mentor, the structure of 1-year clinical psychology training sites limits the development of transformational supervisory relationships during the training year. Interns and fellows often have multiple short-term clinical rotations throughout the year and are assigned different supervisors at each rotation change (Karel & Stead, 2011). This leaves most supervisors with only a few months to work with a trainee, which is insufficient time to develop a more transformational supervisory relationship (Karel & Stead, 2011).…”
Section: Distinction Between Mentorship and Supervisionmentioning
confidence: 99%
“…It is common to use the terms mentor and supervisor interchangeably as supervisors are often asked to provide mentoring to their trainees. There is often overlap between the duties of a mentor and supervisor; however, important differences also distinguish each position (Karel & Stead, 2011). The relationship one has with a mentor is characterized by shared intent and higher levels of involvement by both the mentor and mentee, more than in other work relationships such as those found between a supervisor and supervisee (Kaslow & Mascaro, 2007; Mertz, 2004).…”
Section: Distinction Between Mentorship and Supervisionmentioning
confidence: 99%
“…Mentoring in higher education settings has typically involved a more advanced professional providing support to a student. This might occur through provision of psychosocial support around difficulties faced during training and in particular the adjustment and socialization to the education program, the development of professionally valued knowledge and skills, clarification of career pathways and the development of professional networks (Clark et al , 2000; Karel and Stead, 2011; Taylor and Neimeyer, 2009).…”
mentioning
confidence: 99%
“…academic results, future career progression, self-efficacy and well-being). Studies of mentoring in psychology higher education have suggested that common desirable interventions should include direct skill training or instruction, acceptance, support and encouragement (Clark et al , 2000; Dickinson and Johnson, 2000; Karel and Stead, 2011; Murdock et al , 2013; Johnson, 2014). Desirable outcomes have also been identified.…”
mentioning
confidence: 99%